Environmentally assisted fatigue crack nucleation in Ti–6Al–2Sn–4Zr–6Mo. (July 2015) - Chapman, T.P.; Chater, R.J.; Saunders, E.A.; Walker, A.M.; Lindley, T.C.; Dye, D.
Highlights: A blue-coloured corrosion fatigue cracking initiation feature was observed in fatigue specimens of Ti-6246. It was investigated using secondary ion mass spectrometry (SIMS) and STEM-EDX. It was associated with Cl and O, with an associated Na and Cl-containing surface defect. It was determined to be caused by Hot Salt Stress Corrosion Cracking (HSSCC). A theory of HSSCC is presented, explaining why HSSCC is not usually observed in service. Abstract: An unexplained feature was observed at the fatigue crack origin of a number of α / β titanium specimens tested at 450 °C in the low cycle fatigue regime. The origin was discoloured blue but this was not a result of temper colouration; this feature sometimes resulted in large reductions in fatigue lives. A number of specimens were examined to determine the cause and formation mechanism of these "blue spots." This feature was associated with elevated oxygen and chloride levels and the presence of sodium. A mechanism based on hot-salt stress-corrosion cracking is proposed and the implications for service components are discussed.